(NmIRGOROD(B: [(NpOWESTI(B] / s - (NgOGOLX(B, (NnIKOLAJ wASILXEWI^s ((NmOSKWA(B: s (NdETSKAQ LITERATURA(B, s, 1989)
(Nw KNIGU WHODQT POWESTI gOGOLQ (B"(NsTAROSWETSKIE POME]IKI(B", "(NtARAS bULXBA(B", "(NwIJ(B" (NI (B"(NpOWESTX O TOM(B, (NKAK POSSORILSQ iWAN iWANOWI^ S iWANOM nIKIFOROWI^EM(B", (NSOSTAWLQ@]IE CIKL POD NAZWANIEM (B"(NmIRGOROD(B".s
rus
Keywords: (NpOWESTI I RASSKAZYs